1987
DOI: 10.1002/gps.930020205
|View full text |Cite
|
Sign up to set email alerts
|

Late paraphrenia: Neuropsychological impairment and structural brain abnormalities on computed tomography

Abstract: Forty-three patients with 'late paraphrenia' were subjected to detailed clinical and psychological assessment and computed tomography (CT). The paraphrenics had significantly larger lateral cerebral ventricles and greater cognitive deficits than a group of 40 age-matched normal volunteers. Group comparisons within the patients, between those with particularly large ventricular brain ratio (VBR) (equal or more than two standard deviations above the control mean) and the rest of the group, showed that the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 35 publications
2
76
1
Order By: Relevance
“…Holden 22 found that a subgroup of patients with an onset of psychosis after 60 years, i.e., 'very-late-onset', had an 'organic' form of illness with a relatively poor outcome. In contrast, Naguib &Levy 36 found that, although cognitive deficits were noted in 47 'late paraphrenia' patients, even after a 3.7 year follow-up period these had still not progressed to a stage which would warrant a diagnosis of dementia. In terms of functional outcome, Häfner et al 15 suggested that developmental maturity in late-onset patients might account for less social decline than that experienced by younger psychotic patients.…”
Section: Treatment and Longitudinal Coursementioning
confidence: 89%
“…Holden 22 found that a subgroup of patients with an onset of psychosis after 60 years, i.e., 'very-late-onset', had an 'organic' form of illness with a relatively poor outcome. In contrast, Naguib &Levy 36 found that, although cognitive deficits were noted in 47 'late paraphrenia' patients, even after a 3.7 year follow-up period these had still not progressed to a stage which would warrant a diagnosis of dementia. In terms of functional outcome, Häfner et al 15 suggested that developmental maturity in late-onset patients might account for less social decline than that experienced by younger psychotic patients.…”
Section: Treatment and Longitudinal Coursementioning
confidence: 89%
“…Such personality features were repeatedly found, especially by Kay et al [8], in a comparison of late paraphrenic and depressive patients. Paucity of children, hearing impairment and discriminating early-life experiences have been reported as additional risk factors [4,7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, a restricted social life and the kind of life events shortly preceding the majority of depressions are common experiences of all elderly people; since only a few develop depressive or paranoid illness, a personality or biological predisposition must also be searched for. The role of organic factors such as subtle structural brain damage or cognitive impairment has been investigated in both kinds of disorder in a growing number of studies [1][2][3][4]. The present study was designed to examine patterns of relations and personality which could result in a specific vulnerability to environmental stresses of old age, leading to different kinds of decompensation and mental disorder.…”
Section: Introductionmentioning
confidence: 99%
“…It would seem reasonable to assume that those patients with greater cognitive deficits might be more at risk of subsequently developing dementia [17], however some studies negated the finding [18]. As this patient did not have any cognitive deficits, good prognosis is expected in him.…”
Section: Discussionmentioning
confidence: 90%